Does CEO fitness matter? - Peter Limbach; Florian Sonnenburg (University of Cologne, Centre for Financial Research (CFR), 2015)
This study provides evidence suggesting that CEOs' physical fitness has a positive impact on firm value, consistent with the beneficial effects of fitness on, e.g., cognitive functions, stress coping and job performance. For each of the years 2001 to 2011, we define S&P 1500 CEOs as fit if they finish a marathon. CEO fitness is also associated with higher firm profitability and higher M&A announcement returns. Our identification strategy includes CEO-firm fixed effects, instrumental variables, permutation tests, random effects, and time-varying CEO, firm and industry effects. An additional analysis of sudden CEO deaths, based on a fitness measure not limited to running, confirms our results.
Keywords: G32; G34; J24; 330; CEO heterogeneity; firm value; mergers and acquisitions; physical fitness